Gender Differences in the Effects of Community Violence on Mental Health Outcomes in a Sample of Low‐Income Youth Receiving Psychiatric Care. Issue 3 (5th February 2014) - Javdani, Shabnam; Abdul-Adil, Jaleel; Suarez, Liza; Nichols, Sara R.; Farmer, A. David
Abstract: Previous research suggests that community violence impacts mental health outcomes, but much of this research has not (a) distinguished between different types of community violence, (b) examined gender differences, and (c) focused on youth living in urban poverty. The current study addresses these questions. Participants were 306 youth (23 % girls) and one parent/guardian receiving outpatient psychiatric services for disruptive behavior disorders in a large urban city. Youth and parents reported on youth's experience of different types of community violence (being a direct victim, hearing reports, and witnessing violence), and whether violence was directed toward a stranger or familiar. Outcomes included youth externalizing, internalizing, and posttraumatic stress symptoms assessed via parent and youth reports. Being a direct victim of violence accords risk for all mental health outcomes similarly for both boys and girls. However, gender differences emerged with respect to indirect violence, such that girls who hear reports of violence against people they know are at increased risk for all assessed mental health outcomes, and girls who witness violence against familiars are at increased risk for externalizing mental health symptoms in particular. There are gender differences in violence‐related mental health etiology, with implications for intervention assessment and design.